2023
DOI: 10.32604/csse.2023.034915
|View full text |Cite
|
Sign up to set email alerts
|

A Derivative Matrix-Based Covert Communication Method in Blockchain

Abstract: The data in the blockchain cannot be tampered with and the users are anonymous, which enables the blockchain to be a natural carrier for covert communication. However, the existing methods of covert communication in blockchain suffer from the predefined channel structure, the capacity of a single transaction is not high, and the fixed transaction behaviors will lower the concealment of the communication channel. Therefore, this paper proposes a derivation matrix-based covert communication method in blockchain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Wide access, large capacity covert channels, information concealment and identity anonymity, and resilient communication channels are among the benefits of blockchain technology for covert communication. Zang et al [2] investigated covert channels across several blockchain layers and identified six types of covert channels in contract layer, network layer, data layer, and motivation layer of blockchain. A great medium for covert communication is the blockchain network [28].…”
Section: Covert Channels and Modern Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Wide access, large capacity covert channels, information concealment and identity anonymity, and resilient communication channels are among the benefits of blockchain technology for covert communication. Zang et al [2] investigated covert channels across several blockchain layers and identified six types of covert channels in contract layer, network layer, data layer, and motivation layer of blockchain. A great medium for covert communication is the blockchain network [28].…”
Section: Covert Channels and Modern Technologymentioning
confidence: 99%
“…A significant area of study in information concealment is covert communication, which uses hidden routes to send information covertly. When people are communicating covertly, their relationship can be safeguarded and confidential information cannot be reached, detected, or recovered by unauthorized parties [2]. On the other hand, a covert channel provides an open avenue for hackers to spread destructive activity or leak private information without being discovered [3].…”
Section: Introductionmentioning
confidence: 99%
“…16 If the majority of codes reach a valid signature consensus, a new block of transactions is accepted into the ledger, and the new block is added to the transaction chain. 17 If the majority disapproves of the addition or modification of a ledger entry, it is rejected and not added to the chain. This distributed consensus model is what allows blockchain to run as a distributed ledger without the need for some authority, hence, valid and invalid data can be identified.…”
Section: Discourse On Blockchain Integration In Halal Traceabilitymentioning
confidence: 99%